Assessment of the impact of salvaging the Costa Concordia wreck on the deep coralligenous habitats. (September 2017) - Casoli, E.; Ventura, D.; Cutroneo, L.; Capello, M.; Jona-Lasinio, G.; Rinaldi, R.; Criscoli, A.; Belluscio, A.; Ardizzone, G.D.
Abstract: The coralligenous habitats found in the Mediterranean Sea are hotspots comparable in biodiversity to tropical reefs. Coralligenous reefs are vulnerable to many human pressures, thus they are among the most threatened habitats in the Mediterranean Sea. In this study, we assessed the impacts on coralligenous habitats of activities associated with salvaging the wreck of the Costa Concordia cruise ship. After its partial foundering in 2012, the Costa Concordia remained adjacent to the eastern coast of Giglio Island (Tuscany, Italy), in the Tyrrhenian Sea, for over two years. Its salvage required high-impact engineering works, during the course of which monitoring of benthic communities was undertaken. We performed Rapid Visual Assessment (RVA) sampling (using recorded video) from 17 stations located between 35 and 76 m depth and characterized by coralligenous habitats. Sampling activity was performed during the summers of 2012, 2013, and 2014. In parallel, chemical and physical water parameters were measured continuously from summer 2012 to the end of summer 2014, in order to detect any perturbation in natural conditions caused by salvage activities. We assessed the ecological quality of coralligenous habitats by applying the COARSE (COralligenous Assessment by ReefScape Estimate) index, based on the RVA approach. Slight modifications were applied to one of the descriptors of the COARSE index in order to adjust for study site features. There was clear evidence of a reduction in coralligenous habitats quality. Assemblages, slope, type of pressure, and distance from the source of disturbance played a pivotal role in characterizing bottom quality. The index was shown to have an easy and cost-effective application, even in waters deeper than its calibration specification; furthermore, the modification reported here may increase its potential applications.